Pelatihan Public Speaking Untuk Dakwah Pada Santri Dan Santriwati Pondok Pesantren Arrahmah Kota Jambi - Nurfazillah; Fitri Ana Siregar; Urwawuska Ladini; Saldi Yulistian; Latusi Anggriani; Angger Hidayat; Zakiyatunnisa Al Mubarokah (CV. Multi Kreasi Media, 2023)
Islamic boarding schools are one of the Islamic religious education institutions in Indonesia, consisting of mosques, students, pondoks, kiai, and yellow books in an effort to educate and maintain religious values and norms for the community, one of which is the Arrahmah Litahfiizhil Qur'an Alkarim Islamic Boarding School in Jambi. Based on the results of the observations made, it was found that most of the students had not mastered public speaking, so they did not dare to appear in front of the general public to preach, so that became the basis for the need for public speaking training for Santri and Santriwati at the Islamic Boarding School. This public speaking activity went through several stages, including; observation, orientation, introduction of material, practice, and evaluation. In general, the implementation of this community service activity has been going well thanks to the cooperation between the committees and the support of various parties. However, there were a number of things to note after the activity took place, namely, that the training participants needed continuous assistance after this activity because there were still some students who did not understand terms in foreign languages.